Analysis of Errors in Constructing Arabic Sentences among MPU22362 Students, Sultan Idris Shah Polytechnic - Sanusi, Nur Hidayati (Semarak International Journal of Current Research in Language and Human Studies, 2026)
This study investigates students’ errors in mastering two fundamental Arabic sentence structures, namely Jumlah Ismiyyah and Jumlah Fi‘liyyah. The study aims to identify students’ ability to distinguish between the two sentence types, analyse syntactic errors in constructing basic nominal sentences, and examine morphological errors during the transformation of Jumlah Ismiyyah into Jumlah Fi‘liyyah. A qualitative error-analysis design was employed involving 24 students from a DIF3B class enrolled in the MPU22362 Arabic for Muamalat course. Data were collected through a written diagnostic test consisting of sentence identification, sentence transformation, and basic sentence construction tasks. The findings indicate a moderate level of overall ability, with 75% of students correctly identifying sentence types. The most dominant syntactic error involved misuse of Ma‘rifah and Nakirah forms (54.2%), while the most critical morphological error was the failure to apply correct verb subject agreement in verbal sentences, particularly the use of singular verb forms when the subject follows the verb. These results suggest persistent difficulties in the practical application of grammatical rules rather than isolated errors. In conclusion, the study indicates that students’ grammatical errors reflect limitations in integrating syntactic and morphological knowledge in practical language use. The findings highlight the pedagogical value of emphasising integrated ṣarf–naḥw analysis, guided sentence transformation exercises and corrective feedback to strengthen learners’ mastery of basic Arabic sentence structures. Future research incorporating qualitative methods is recommended to explore learners’ cognitive processes in greater depth.